Religious Knowledge and Breastfeeding Mothers Status in Indonesia - Andi Faradilah (Universitas Islam Negeri Alauddin Makassar, 2017)
The high rate of stunting is one of the nutritional problems in Indonesia. Stunting is a condition in which Indonesian children do not achieve optimal height according to the age. Attention to the first 1,000 days of life particularly promotion of breast-feeding for two full years is regarded as a solution to solve this problem. This study aims to examine the relationship of religious knowledge related with breastfeeding encouragement in the Koran and the status of breastfeeding mothers. This research was a quantitative and qualitative research. The data collection was done by cross sectional in Makassar and Palopo on mothers of children aged 12-36 months. The results showed that there were 98 mothers fulfill selection criteria. 83 mothers (84.7%) knew the advice to breastfeed in the Qur'an, while 15 mothers (15.3%) did not know. In addition, there were 57 mothers (58.2%) still breast-feeding, and 41 (41.8%) had stopped breastfeeding by p = 0.007. Finally, this study confirmed that religious suggestion to enhance breast-feeding for two years proved to be a boost to the mother to breastfeed her child.